Pengaruh Motivasi dan Persepsi Biaya Pendidikan pada Minat Mahasiswa Mengikuti Pendidikan Magister Akuntansi - Surya B., I Gede Agus Dicky; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2019)
Master of Accounting is a secondary education in higher education to get a master's  degree. The purpose of this study was to determine the effect of quality motivation, career  motivation, economic motivation, and perceptions of education costs on the interest of  students attending the Master of Accounting education. The population in this study were  all accounting students at the Faculty of Economics and Businessclass of 2015 many as  298. The sampling technique used was purposive sampling method. The number of samples  determined is 171 samples. Methods of collecting data using a questionnaire. The data  analysis technique used is multiple linear regression analysis. The results of the analysis  show that quality, career, and economic motivation have a positive effect on students'  interest in taking part in the Accounting Master's education, while the perception of  education costs has a negative effect on the interest of students attending the Master of  Accounting. Keywords: Quality motivation, career motivation, economic motivation, perception of  education costs, student interest.